KLF7 promotes preadipocyte proliferation via activation of the Akt signaling pathway by Cis-regulating CDKN3 - Jia Ziqiu; Jin Zhao; Shao Shuli; Xu Hu; Li Wen; Khan Mahmood; Wang Weiyu; Zhang Weiwei; Sun Yingning (Acta Biochimica et Biophysica Sinica, 2022)
Krüppel-like transcription factor 7 (KLF7) promotes preadipocyte proliferation; however, its target gene in this process has not yet been identified. Using KLF7 ChIP-seq analysis, we previously showed that a KLF7-binding peak is present upstream of the cyclin-dependent kinase inhibitor 3 gene ( CDKN3) in chicken preadipocytes. In the present study, we identify CDKN3 as a target gene of KLF7 that mediates the effects of KLF7 on preadipocyte proliferation. Furthermore, 5′-truncating mutation analysis shows that the minimal promoter is located between nt –160 and nt –7 (relative to the translation initiation codon ATG) of CDKN3. KLF7 overexpression increases CDKN3 promoter activity in the DF-1 and immortalized chicken preadipocyte (ICP1) cell lines. Deletion of the putative binding site of KLF7 abolishes the promotive effect of KLF7 overexpression on CDKN3 promoter activity. Moreover, CDKN3 knockdown and overexpression assays reveal that CDKN3 enhances ICP1 cell proliferation. Flow cytometry analysis shows that CDKN3 accelerates the G1/S transition. Furthermore, we find that KLF7 promotes ICP1 cell proliferation via Akt phosphorylation by regulating CDKN3. Taken together, our results suggest that KLF7 promotes preadipocyte proliferation by activating the Akt signaling pathway by cis-regulating CDKN3, thus driving the G1/S transition.